The Effect of Medicine Ball Throwing Exercises on Power Throw-In in U-15 Soccer Players of Ssb Untag Rosita Sidoarjo - Hikmal Zhafar Santoso; Luqmanul Hakim (Green Publisher Indonesia, 2026)
Training is a planned and systematic process aimed at gradually and continuously improving the physical, technical, tactical, and mental abilities of athletes. One of the physical components that plays a significant role in football is the explosive power of the arm muscles, particularly in executing throw-in techniques. A strong and well-directed throw-in can provide a tactical advantage for the team. One exercise method believed to be effective in enhancing arm muscle power is training using medicine balls. This study aims to determine the effect of throwing exercises with medicine balls on the throw-in power of U-15 football players at SSB Untag Rosita Sidoarjo. The research employed a pre-experimental method using a One Group Pretest–Posttest Design. The study population consisted of 15 U-15 football players from SSB Untag Rosita Sidoarjo, with samples selected through total sampling. The data collection instrument used was the throw-in distance test, measured before and after the training intervention. Data were analyzed using the Paired Sample t-test with a significance level of 0.05.The results showed an increase in the average throw-in distance after the training using medicine balls. Based on the results of the Paired Sample t-test, a significance value (p-value) < 0.05 was obtained, leading to the rejection of H? and the acceptance of H?. Thus, it can be concluded that throwing exercises using medicine balls have a significant effect on improving the throw-in power of U-15 football players at SSB Untag Rosita Sidoarjo.